2018 IEEE International Symposium on Broadband Multimedia Systems and Broadcasting (BMSB) 2018
DOI: 10.1109/bmsb.2018.8436788
|View full text |Cite
|
Sign up to set email alerts
|

700 MHz Band LTE Uplink Interference to DTT Reception System Cabling

Abstract: This paper studies the shielded screening attenuation of consumer-grade digital terrestrial television (DTT) antenna coaxial cables and presents a measurement campaign to determine their vulnerability to interference originating from uplink traffic of a nearby Long Term Evolution (LTE) user equipment (UE) operating on the 700 MHz frequency band. The interference scenario is novel as the LTE uplink traffic on the 700 MHz band is significantly closer in frequency to the DTT transmissions than previously with the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…The results of [28] indicated that interfering LTE-DL signals have a minimal impact on portable DTTB indoor reception with various configurations in adjacent bands. In [29], the study measured the shielding performance of consumer DTTB antenna cables in the laboratory, finding variations of up to 60 dB. It assessed the susceptibility to interference from LTE uplink traffic in the 700 MHz band.…”
Section: Introductionmentioning
confidence: 99%
“…The results of [28] indicated that interfering LTE-DL signals have a minimal impact on portable DTTB indoor reception with various configurations in adjacent bands. In [29], the study measured the shielding performance of consumer DTTB antenna cables in the laboratory, finding variations of up to 60 dB. It assessed the susceptibility to interference from LTE uplink traffic in the 700 MHz band.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [35] conducted laboratory measurements to investigate LTE uplink interference on coaxial cables connecting TV sets to digital TV aerial sockets. Ref.…”
Section: Introductionmentioning
confidence: 99%